Contamination of Vibrio parahaemolyticus in crayfish for sale - Wu, Kui; Zou, Dazhao; Long, Yongyan; Xue, Lin; Shuai, Shufen; Tian, Feiyan; Li, Mei; Fan, Guoyin; Zheng, Yangyun; Sun, Xiangrong; Wang, Wei; Wang, Li; et al. (Frontiers in Microbiology, 2024)
Crayfish (Procambarus clarkii) are economically important freshwater crustaceans. With the growth of the crayfish industry, the associated food-safety risks should be seriously considered. Although Vibrio parahaemolyticus is commonly recognized as a halophilic foodborne pathogen associated with seafood, it has been found to be a major pathogen in crayfish-associated food poisoning cases. In this study, the V. parahaemolyticus contamination level in crayfish production-sale chain was investigated using crayfish and environmental samples collected from crayfish farms and markets. Serious V. parahaemolyticus contamination (detection rate of 66%) was found in the entire crayfish production-sale chain, while the V. parahaemolyticus contamination level of the market samples was extremely high (detection rate of 92%). The V. parahaemolyticus detection rate of crayfish surface was similar to that of whole crayfish, indicating that crayfish surface was important for V. parahaemolyticus contamination. The simulation experiments of crayfish for sale being contaminated by different V. parahaemolyticus sources were performed. All the contamination sources, containing V. parahaemolyticus-positive tank, water, and crayfish, were found to be efficient to contaminate crayfish. The crayfish tank displayed the most significant contaminating role, while the water seemed to inhibit the V. parahaemolyticus contamination. The contamination extent of the crayfish increased with the number of V. parahaemolyticus cells the tank carried and the contact time of the crayfish and the tank, but decreased with the time that the crayfish were maintained in the water. It was also confirmed that the crayfish surface was more susceptible to V. parahaemolyticus contamination than the crayfish intestine. Furthermore, the adsorption of V. parahaemolyticus onto the crayfish shell was analyzed. Over 90% of the V. parahaemolyticus cells were adsorbed onto the crayfish shell in 6 h, indicating a significant adsorption effect between V. parahaemolyticus and the crayfish shell. In conclusion, within a water-free sale style, the fresh crayfish for sale in aquatic products markets uses its shell to capture V. parahaemolyticus cells from the V. parahaemolyticus-abundant environments. The V. parahaemolyticus contamination in crayfish for sale exacerbates the crayfish-associated food-safety risk. This study sheds light on V. parahaemolyticus control and prevention in crayfish industry.